Optimizing Radio Broadcasting in the Digital Age: Effective Planning and Management Strategies - Harliantara, Harliantara; Didik Sugeng Widiarto; Ahmadi; Bahar Ozturk (Universitas Multimedia Nusantara, 2025)
In the contemporary digital era, radio stations are confronted with novel challenges and opportunities that require more effective planning and management strategies. This study explored the significance of comprehensive planning and management in optimising radio broadcasting, particularly in the context of evolving technology and shifting audience preferences. Through an analysis of case studies and current research, this study identifies the key components of broadcast management planning, including programming strategy, resource management, and budget management. In addition, it examines the challenges confronting radio stations in the digital age, such as their adaptation to new technologies, industry competition, and evolving audience preferences. Adopting a holistic stance, this study proffers pragmatic recommendations for radio stations to enhance their operational efficiency, content quality, and audience engagement. The findings of this study are anticipated to provide guidance to broadcasting professionals, enabling them to plan and manage their operations more efficaciously in the digital era.